THE EFFECT OF EXPENDITURE TREASURER ROLE ON THE QUALITY OF FINANCIAL STATEMENTS IN THE REGIONAL PUBLIC SERVICE AGENCY OF HEALTH SERVICES IN BANDUNG DISTRICT - Tresnawati, Rina (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of the role of the expenditure treasurer on the quality of financial reports in the regional public service agency of health services in Bandung District The background of this research is that there is still a recording error that is carried out by the treasurer of expenditure so that it affects the financial statements. The method used in this study is explanatory research using simple regression analysis. The coefficient of determination and hypothesis testing use the t test and data processing assisted by SPSS software. The sample in this study is based on the purposive sampling method. In this study, the number of samples examined was 31 public service agencies in the health service area in Bandung District, with a total of 31 respondents. The results of this study indicate that the role of expenditure treasurer has a significant effect on the quality of financial statements. In addition, the role of the expenditure treasurer was able to influence the quality of the financial services report of the health service public services in Bandung District.